2018
DOI: 10.1002/jlb.4a0917-369rr
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cell-derived RELMα regulates hookworm immunity through effects on macrophages

Abstract: Resistin-like molecule α (RELMα) is a highly secreted protein in type 2 (Th2) cytokine-induced inflammation including helminth infection and allergy. In infection with Nippostrongylus brasiliensis (Nb), RELMα dampens Th2 inflammatory responses. RELMα is expressed by immune cells, and by epithelial cells (EC); however, the functional impact of immune versus EC-derived RELMα is unknown. We generated bone marrow (BM) chimeras that were RELMα deficient (RELMα ) in BM or non BM cells and infected them with Nb. Non … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 75 publications
(135 reference statements)
1
25
1
Order By: Relevance
“…However, it remains to be seen how tightly linked Ym1’s functions are to its ability to induce RELMα. In addition, recent data suggest that macrophage-derived RELMα is critical for its regulatory function [64] and we have yet to establish whether the ability of Ym1 to induce RELMα is restricted to epithelial cells. Finally, the changes in Ym1 function over time may largely relate to its ability to bind ECM, the properties of which will change over the course of an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be seen how tightly linked Ym1’s functions are to its ability to induce RELMα. In addition, recent data suggest that macrophage-derived RELMα is critical for its regulatory function [64] and we have yet to establish whether the ability of Ym1 to induce RELMα is restricted to epithelial cells. Finally, the changes in Ym1 function over time may largely relate to its ability to bind ECM, the properties of which will change over the course of an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…RELMα activates the enzyme lysyl hydrolase 2 ( Plod2 ), which mediates optimal collagen cross‐linking . Additionally, macrophage‐derived RELMα was implicated in dampening lung inflammation and promoting tissue repair in a model of helminth infection‐induced lung injury with rodent hookworm Nippostrongylus brasiliensis . In this model, gene expression analysis of RELMα‐treated lung macrophages revealed that RELMα promoted expression of genes involved in extracellular matrix remodeling: matrix metalloproteinase 9 ( Mmp9 ), integrin beta 1 ( Itgb1 ) and junctional adhesion molecule A ( F11r ).…”
Section: Wound‐healing Macrophage Activation and Functionmentioning
confidence: 99%
“…Studies in pulmonary inflammation, hypertension and fibrosis, point to an inflammatory function for RELMa by promoting immune cell recruitment, fibroblast activation and proliferation associated with pathogenic fibrosis (20,21). On the other hand, in response to tissue migratory helminth parasites, RELMa critically prevents fatal lung tissue damage, granulomatous inflammation, and promotes tissue repair (22)(23)(24)(25)(26)(27)(28). Downstream regulatory mechanisms for RELMa include limiting CD4 + T cell polarization, promoting anti-inflammatory responses, and mediating collagen cross-linking associated with tissue healing (26,29,30).…”
Section: Introductionmentioning
confidence: 99%